The Utilization of Soybean Hulls as Energy Resources on Ration Local Sheep - Rimbawanto, EA; Iriyanti, Ning (ANIMAL PRODUCTION, 2001)
An experiment was conducted to investigate the effects of soybean hulls as a ration in twenty seven rams. The animal had a mean of live weight of 12.863 ± 1.934 kg. Levels of soybean hulls were 0, 50, and 100 %  or 0,25, and 50 % in ration dry matter basis and rations were  iso-nitrogenous. The experiment were use Completely Randomized Design, data collected was analyzed using analysis of variance and polynomial orthogonal test.  Inclusion of soybean hulls in 50% ration dry matter had no effect on daily live weight gain (90.65±20.88 g), nitrogen, calcium and phosphor balances positive. However, dry matter consumption tended to increase linearly and as soybean hulls level increase in the ration (P<0.01). The digestible energy and NDF significantly decrease linearly (P<0.01), whereas intake of the energy was similar i.e. 122±0.39, 1.44±0.17, and 1.23±0.19 Mcal/day but NDF tended to increase for ration containing 0, 25, 50% of soybean hulls, respectively. The digestible crude protein is significantly quadratic (P<0.01), due to the release of energy and N are synchronized in 25% of soybean hulls in ration dry matter. It was concluded that soybean hulls can be used as a sources of energy and substitute for corn. (Animal Production 3(1): 5-11 (2001) Key Words: Local ram, soybean hulls, live weight gain, digestibility